378 Growth in Gastroschisis: a prospective, observational cohort study. (17th August 2022) - Sewell, Edward; Hall, Nigel
Abstract : Aims: Existing evidence of growth patterns in infants with gastroschisis is largely retrospective. This study uses prospectively collected anthropometric data from the pre- and postnatal periods (up to 1 year old) to determine growth patterns in a cohort of infants with gastroschisis. This aims of this study were to characterise a) prenatal growth, and b) postnatal growth, in infants with gastroschisis. Methods: Explorative analysis of prospectively collected pre- and postnatal anthropometric data for a cohort of infants with gastroschisis (n=19). Prenatal measurements of mean femur length (FL), thoracic circumference (TC) and head circumference (HC) were compared with corresponding data from the Southampton Women's Survey (SWS) (n=3173), a control cohort of infants from the Wessex region. Postnatal data for weight, height and head circumference were converted to standard deviation scores for comparison with the Health for all children clinical growth standard (HFAC, 1990) at 5 separate time points: birth, discharge, 3 months, 6 months and 12 months. Results: At 19 weeks gestational age (GA), mean TC (130.4 vs 131.4, p = 0.72) was not significantly decreased in the GIG cohort and mean HC (173.9 vs 168.5, p = 0.02) and FL (32.2 vs 30.7, p < 0.01) were significantly greater than the SWS mean at the same gestation. At 34 weeks GA. difference in mean TC (219.2mm vs 248.4 mm, p < 0.0001), FL (62.1 vs 64.8, p < 0.0001) and HC (310.8 vs 317.5, p = 0.02) were all statistically significant at 34 weeks gestational age ( figure 1 ). At birth, mean cohort weight SDS (-0.53), length SDS (-1.90) and head circumference SDS (-0.22) were all below the HFAC mean, corrected for gestational age at birth. Postnatal trends showed an inpatient decline in weight SDS from -0.56 at birth to -1.33 at discharge, followed by an increase to -1.05 at 3 months and -0.77 at 12 months. Length SDS increased from -1.90 at birth to -1.50 at discharge, and to -0.01 at 12 months. HC SDS decreased from -0.22 at birth to -0.55 at discharge. Mean HC SDS at 12 months was -0.57 ( figure 2 ). Conclusion: The findings of this study support 4 main conclusions: 1) increase in femur length and thoracic circumference between 19 and 34 weeks is reduced in the study cohort compared to the SWS cohort, indicating that a prenatal growth deficit occurs in this time period. 2) Mean weight, length and head circumference at birth are all below the HFAC mean (corrected for gestational age), suggesting that prenatal growth impairment affects all growth indices, however linear growth is more heavily affected than weight and head circumference. 3) There are different growth trends in the first year for weight, length and head circumference. Regarding weight and length, the results of this study indicate that catch-up growth occurs in the first year of life. 4) Pre- and postnatal data indicate that head circumference is less significantly impaired than other growth indices, possibly indicating there is preservation of head circumference despite deficits in other parameters.